Wideband Sparse Array Synthesis With Frequency-Invariant Pencil Beampatterns Using l0-Norm Minimization - Wang, Caizhi; Chen, Huawei (IEEE transactions on antennas and propagation, 2025)
This paper studies wideband sparse array synthesis with frequency-invariant pencil beampatterns by joint sparsification of array elements and beamformer tap weights. Unlike the popularly used sparse synthesis methods based on reweighted l 1 -norm minimization, which may lead to less sparse solutions due to the approximation of l 0 -norm by weighted l 1 -norm, this paper devotes to synthesize wideband sparse arrays by directly using the l 0 -norm minimization. To effectively address the l 0 -norm minimization based synthesis problem, an alternating direction method of multipliers (ADMM) solution using the iterative hard thresholding is developed. Under the ADMM framework, the original high-dimensional optimization problem is decomposed into several easier to handle subproblems. The closed-form solution to each subproblem is derived and thus yields computationally efficient synthesis of wideband sparse arrays. Numerical results demonstrate that the proposed synthesis can save more array elements and beamformer tap weights than its existing counterpart. Moreover, the proposed synthesis is also shown to be much more efficient in terms of synthesis time.